Fuzzy structural risk of default for banks in Southern Africa - Ephraim Matanda; Eriyoti Chikodza; Farai Kwenda (Cogent Economics & Finance, 2022)
This paper proposes and examines a new structural risk of default model for banks in frictional and fuzzy financial markets. It is motivated by the need to fill the shortcomings of probability-based credit risk metric models that are characterised by unrealistic assumptions such as crisply precise and constant risk-free rates of return. The problem investigated here specifically proposes a new Kealhofer-Merton-Vasicek (KMV)-type model for estimation of the risk of default for banks extended for both market friction represented by transaction costs and uncertainty modelled by fuzziness. The novel risk of default model is then validated using cross-sectional financial data of eight commercial banks drawn from several emerging economies in Southern Africa. The results from the proposed model are fairly stable and consistent compared to those from hazard function and structural credit risk models currently used in the markets. The model is relevant in that it fairly captures practical conditions faced by banks that influence their risks of default in their quest to improve financial performance and shareholders' wealth. The study recommends that banks in frictional and fuzzy financial markets, such as those in emerging economies, can adopt and implement the proposed risk of the default model.
Keywords: C13; G24; 330; fuzziness; fuzzy financial markets; market friction; risk metrics; risk of default